Community Based Edupreneur Electronic Word of Mouth in Improving the Brand Image of Online Stores (Lembaran Ilmu Kependidikan, 2023)
Community Based Edupreneur is increasingly popular moment This Because driven by increasing internet users increase. Opportunity This open opportunity for online business that causes competition the more tight. Brand image is a lot of strategy used by companies For win competition. For know influencing factors brand image online shop done studies empirical with objective For  analyze influence direct electronic customer satisfaction, electronic word of mouth against online store brand image, as well analyze influence No direct e-customer satisfaction to brand image online store via electronic word of mouth. Data collected from 200 consumers online store and in analysis with method Structural Equalization Modeling. Results of data processing for test the proposed hypothesis is known that For increase brand image online shop, supposedly manager online store focus on how increase amount consumers who will give review about online shop / push electronic word of mouth. Whereas electronic word of mouth is influenced by electronic customer satisfaction.